Mapping Commercial Web 2.0 Worlds: Towards a New Critical Ontogenesis - Kenneth Werbin; Greg Elmer; Fenwick McKelvey; Ganaele Langlois (Open Humanities Press, 2009)
At the 2007 International Communication Association Conference, Web 2.0 was highlighted as an emergent topic of research with a keynote panel entitled 'What's so Significant about Social Networking? Web 2.0 and its Critical Potentials'. One of the thought-provoking moments during the panel was the juxtaposition of two very different and at first, contradictory theoretical approaches to the relationships between Web 2.0 and user-generated content. While Henry Jenkins focused on the democratic potential of online participatory culture as enabling new modes of knowledge production, Titziana Terranova argued for a post-Marxist perspective on Web 2.0 as a site of cultural colonization and expansion of new forms of capitalization on culture, affect and knowledge. The juxtaposition of these two very different critical approaches did not simply rehash the old divide between cultural theory, particularly active audience theory, and post-Marxist critical theory; rather, this debate over Web 2.0 suggested new possibilities for the synthesis and continued development of both sets of critiques. In other words, the event reinforced our belief that corporate colonization arguments do not provide an entirely adequate model for understanding Web 2.0. After all, commercial Web 2.0 spaces such as Facebook, YouTube and MySpace are important sites of cultural exchange and political discussion, in part because they almost entirely rely on user-generated content to exist.